Modulation of Antioxidant Enzyme Expression of In Vitro Culture-Derived Reticulocytes - Hannah D. Langlands; Deborah K. Shoemark; Ashley M. Toye (MDPI AG, 2024)
The regulation of reactive oxygen species (ROS) in red blood cells (RBCs) is crucial for maintaining functionality and lifespan. Indeed, dysregulated ROS occurs in haematological diseases such as sickle cell disease and β-thalassaemia. In order to combat this, RBCs possess high levels of protective antioxidant enzymes. We aimed to further boost RBC antioxidant capacity by overexpressing peroxiredoxin (Prxs) and glutathione peroxidase (GPxs) enzymes. Multiple antioxidant enzyme cDNAs were individually overexpressed in expanding immortalised erythroblasts using lentivirus, including Prx isoforms 1, 2, and 6 and GPx isoforms 1 and 4. Enhancing Prx protein expression proved straightforward, but GPx overexpression required modifications. For GPx4, these modifications included adding a SECIS element in the 3'UTR, the removal of a mitochondrial-targeting sequence, and removing putative ubiquitination sites. Culture-derived reticulocytes exhibiting enhanced levels of Prx and GPx antioxidant proteins were successfully engineered, demonstrating a novel approach to improve RBC resilience to oxidative stress. Further work is needed to explore the activity of these proteins and their impact on RBC metabolism, but this strategy shows promise for improving RBC function in physiological and pathological contexts and during storage for transfusion. Enhancing the antioxidant capacity of reticulocytes has exciting promise for developing culture-derived RBCs with enhanced resistance to oxidative damage and offers new therapeutic interventions in diseases with elevated oxidative stress.